Terrain physical properties derived from orbital data and the first 360 sols of Mars Science Laboratory Curiosity rover observations in Gale Crater. Issue 6 (17th June 2014) - Arvidson, R. E.; Bellutta, P.; Calef, F.; Fraeman, A. A.; Garvin, J. B.; Gasnault, O.; Grant, J. A.; Grotzinger, J. P.; Hamilton, V. E.; Heverly, M.; Iagnemma, K. A.; Johnson, J. R.; et al.
Abstract: Physical properties of terrains encountered by the Curiosity rover during the first 360 sols of operations have been inferred from analysis of the scour zones produced by Sky Crane Landing System engine plumes, wheel touch down dynamics, pits produced by Chemical Camera (ChemCam) laser shots, rover wheel traverses over rocks, the extent of sinkage into soils, and the magnitude and sign of rover‐based slippage during drives. Results have been integrated with morphologic, mineralogic, and thermophysical properties derived from orbital data, and Curiosity‐based measurements, to understand the nature and origin of physical properties of traversed terrains. The hummocky plains (HP) landing site and traverse locations consist of moderately to well‐consolidated bedrock of alluvial origin variably covered by slightly cohesive, hard‐packed basaltic sand and dust, with both embedded and surface‐strewn rock clasts. Rock clasts have been added through local bedrock weathering and impact ejecta emplacement and form a pavement‐like surface in which only small clasts (<5 to 10 cm wide) have been pressed into the soil during wheel passages. The bedded fractured (BF) unit, site of Curiosity's first drilling activity, exposes several alluvial‐lacustrine bedrock units with little to no soil cover and varying degrees of lithification. Small wheel sinkage values (<1 cm) for both HP and BF surfaces demonstrate that compaction resistance countering driven‐wheel thrust has been minimal and that rover slippage while traversing across horizontal surfaces or going uphill, and skid going downhill, have been dominated by terrain tilts and wheel‐surface material shear modulus values. Key Points: Curiosity landing site consolidated bedrock covered by packed sand with clasts Curiosity drill site is alluvial‐lacustrine bedrock unit with little soil cover Rover slip/skid dominated by terrain tilt and wheel‐surface material shear modulus